The Role of Bonus Allocation in Project Investment: An experimental study using Balanced Scorecard (BSC) Training Treatment - Fauziah Rahman; Harry Suharman; Sofik Handoyo (Journal of Accounting Auditing and Business, 2020)
This research aims to determine the role of bonus allocation and balanced scorecard training in the selection of investment projects. This research used a controlled laboratory experiment method with a pretest-posttest control group experimental design which involves two groups, namely the experimental group and the control group. The experiment was carried out on 46 accounting graduate students as participants. The results of this research indicate that in selecting the investment projects, participants tend to comply with the bonus allocation policies and that balanced scorecard training is capable of predisposing participants to select projects that are oriented to long-term benefits by observed to financial and non-financial aspects. This research is specifically expected to contribute in the form of an illustration to the company about the importance of training related to the concepts and assignment techniques as well as an overview of the importance of providing appropriate bonus allocation bases to improve employee performance and evade opportunistic behavior